2013
DOI: 10.5152/jtgga.2013.50133
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of early decline in percentage of β-hCG values between days 0 and 4 after methotrexate therapy in ectopic pregnancy for prediction of treatment success

Abstract: Objective: To evaluate percentage changes in serum beta-human chorionic gonadotropin (β-hCG) values between days 0-1, 0-4 and 0-7 as an indicator of methotrexate therapy success in extra-uterine pregnancies. Material and Methods:Women with ectopic pregnancy treated with single-dose methotrexate therapy between January 2011 and August 2012 were assessed. Recorded data were reviewed electronically from patient files. All women (n=93) with an ectopic pregnancy treated medically with intramuscular methotrexate (50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
1
12
1
4
Order By: Relevance
“…They found that 20% decline was associated with a very high chance of subsequent treatment success, with positive predictive value as high as 97%. 8 However in the present study the mean decline of serum β-hCG more than or equal to 30% was found to have successful outcome. Our study mostly confirms the results of previous studies who reported treatment success of 88-100% in those women with early decline in serum β-hCG between days 0 to 4, however our study had success of 75% this difference in the result may be due to small sample size analyzed.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…They found that 20% decline was associated with a very high chance of subsequent treatment success, with positive predictive value as high as 97%. 8 However in the present study the mean decline of serum β-hCG more than or equal to 30% was found to have successful outcome. Our study mostly confirms the results of previous studies who reported treatment success of 88-100% in those women with early decline in serum β-hCG between days 0 to 4, however our study had success of 75% this difference in the result may be due to small sample size analyzed.…”
Section: Discussioncontrasting
confidence: 61%
“…2,7 A study by Celik et al 8 evaluated the use of percentage decline of serum β-hCG between days 1 to 4 following administration of methotrexate as an indicator of treatment success. They found that 20% decline was associated with a very high chance of subsequent treatment success, with positive predictive value as high as 97%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Ustunyurt et al [17] reported that a 22% decrease in b-hCG level predicted treatment success. Celik et al [18] studied 93 patients and reported a 4.94-fold increase in treatment failure associated with at least a 9.08% decrease in b-hCG levels from Day 1 to Day 4. Following methotrexate administration, a slight increase in b-hCG levels is usually expected in the first few days [18].…”
Section: Discussionmentioning
confidence: 99%
“…Yüksek serum ß-hCG düzeyleri daha önceki iki çalışmada bizimkine benzer tarzda tek etkili prognostik faktör olarak tespit edilirken (6,19) , Kimiaei ve ark. tarafından yapılan çalışmada tek doz metotreksat tedavisinin etkinliğini belirlemede başlangıç ß-hCG değerlerine ek olarak ektopik odak büyüklüğü de önemli olarak tespit edilmiştir (20) bazı çalışmalarda başlangıç ß-hCG değeri yüksekliğine ek olarak başlangıç ve metotreksat sonrası dördüncü gün ß-hCG değerlerindeki düşme düzeyi başarıyı tahminde en önemli gösterge olduğu belirtilmiştir (21,22) . Ayrıca Mungan ve ark.…”
Section: Discussionunclassified